Razón y democracia: La potencial renovación del concepto de aristocracia - Pedro José Izquierdo (Ius Humani. Jornal do direito, 2012)
This article studies the relationship between different kinds of discussion and the roles that they play in the diverse institutions of modern representative democracy. It distinguishes between three kinds of discussion: Platonic dialectic, deliberation, and democratic debate, and places them on a scale of decreasing attunement to rational standards of decision-making. It is argued that the more discussions are attuned to rational standards, the less democratic they become, because the less they are in sync with the mode of discussion that is proper to, and that in fact obtains in the demos. This tension between rational decision-making and democracy is identified as the tension between aristocracy and democracy as it was understood by the vast tradition of political philosophy, and suggests a way in which aristocracy may be reintroduced as a meaningful concept in modern constitutional thought. It is argued that only by acknowledging the existence of an aristocratic quality to rational decision-making is it possible to truly preserve the democratic character of representative institutions.